DISKRESI, LEMBAGA KOMUNIKASI DAN INFORMATIKA DI KOTA YOGYAKARTA - Suwarto, Suwarto (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
The publication of Government Regulation Number: 41 year 2007 regarding the regional organization requires each region to form local ICT government institution. However, but the city of Yogyakarta conducted institutional discretion by not forming the institution. The purpose of this study was to determine why the city of Yogyakarta conducted the discretion by not maintaining the authority of Information and Communication Technology as mandated by the Government Regulation Number: 41 in 2007. The methods used in this research were descriptive and qualitative approach. Data was collected through in-depth interviews and tracking documentation. The techniques of data analysis used were data reduction, data presentation and verification. The results showed that the policy of discretion was taken because there were local capacity and necessity which were not anticipated by the Government Regulation.